Optimal state observation using quadratic boundedness: Application to UAV disturbance estimation - Cayero, Julián; Rotondo, Damiano; Morcego, Bernardo; Puig, Vicenç (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the design of a state observer which guarantees quadratic boundedness of the estimation error. By using quadratic Lyapunov stability analysis, the convergence rate and the ultimate (steady-state) error bounding ellipsoid are identified as the parameters that define the behaviour of the estimation. Then, it is shown that these objectives can be merged in a scalarised objective function with one design parameter, making the design problem convex.
Keywords: disturbance estimation; unmanned aerial vehicles (UAVs); optimal estimation and filtering; system modelling